Insulin receptor substrate-1 is over-expressed in glycogenotic but not in amphophilic preneoplastic hepatic foci induced in rats by N-nitrosomorpholine and dehydroepiandrosterone - Nehrbaß, Dirk; Klimek, Fritz; Bannasch, Peter; Mayer, Doris (Cancer letters, 1999)
Insulin receptor substrate-1 (IRS-1) is over-expressed in preneoplastic glycogenotic hepatic foci (GSF) and is gradually down-regulated during progres…
Gesehen am 18.02.2019